UPAYA PENINGKATAN PENGETAHUAN DAN KETERAMPILAN BANTUAN HIDUP DASAR PADA KASUS KEGAWATDARURATAN BAGI MASYARAKAT UMUM - Wratsangka, Raditya; Krishna Murthi, Aditya; Tungka, Endrico Xavierees; Tjhin, Purnamawati; Primaresti, Arella Fina; Diwa, Puti Maharan (Jurnal Pengabdian Masyarakat Trimedika, 2025)
Sudden cardiac arrest is one pf the leading causes of death that can be prevented through proper initial treatment. this study aims to improve the understanding and skills of the community, especially church officers, in providing Basic Life Support (BLS) through training held on September 14, 2024 at the Hall of the Maria Bunda Karmel Church, West Jakarta. This activity was attended by 70 participants and included materials on cardiac arrest, cardiopulmonary resuscitation (CPR), and handling other emergency cases. The methods used included pre-test and post test to evaluate the increase in participants knowledge. The results showed that after the training, there was a significant increase in knowledge regarding signs of cardiac arrest and first aid procedures, with 100% of respondents being able to identify and provide appropriate assistance. The conclusion of this study emphasizes the importance of regular BLS training to improve community preparedness in dealing with emergency situations, which in turn can reduce morbidity and mortality due to cardiac arrest.